ANALYSIS OF BENEFITS AND POTENTIAL DAMAGE FROM COVID-19 VACCINATION - Y. Park; Y.K. Cho; J. Jung (International Journal of Infectious Diseases, 2023)
Intro: COVID-19 Vaccination has proven to be very effective in preventing infection and progression to severity and death. However, there were concerns about very rare but potentially fatal adverse reactions after vaccination; myocarditis/pericarditis, TTS/VITT et al. It suggested that the evaluation of the two values of personal safety and public benefit is necessary. Methods: The benefit of vaccination was measured by the number of critically ill patients prevented from vaccination. The number of critically ill patients predicted in the future was measured through two Methods: based on a fixed scenario, and using a mathematical model. Damage through vaccination was calculated as the occurrence of TTS/VITT, Myocarditis/Pericarditis, and of severe cases. Findings: The evaluation results on vaccine safety and effectiveness were made in the form of age restrictions for vaccination by each vaccine platform. As a result of the evaluation, the AstraZeneca vaccine was limited to those under the age of 30 but there was no restriction on the age of mRNA vaccination. In addition, the risks and benefits of vaccination for children aged 5-11 years and 12-17 years of age were evaluated respectively, and it was confirmed that the benefits of vaccination outweigh the potential harm in children and adolescents. Conclusion: Our nation has the own policy for COVID 19 vaccination from the results. The pandemic situation has presented a new approach to the benefits and risks of large-scale vaccination. In particular, the method of comparing the risks and benefits of vaccination was considered as a useful method for health communication.